Clinical Characteristics and Eosinophils in Young SARS-CoV-2-Positive Chinese Travelers Returning to Shanghai - Yang, Juan; Zhao, Xiaohui; Liu, Xueyuan; Sun, Wanju; Zhou, Longzhu; Wang, Yongbing; Sui, Haijing (Frontiers in Public Health, 2020)
Background The COVID-19 outbreak, which was first reported in Wuhan of China in December 2019, began to occur in the world, involving over 200 countries now. Methods A total of 37 overseas young and mid-aged people, who were tested SARS-CoV-2 positive upon their return to Shanghai, were enrolled for an analysis of the clinical symptoms, blood routine indexes and lung CT images. Results The clinical symptoms were characterized by fever (51.4%), dry cough (13.5%), expectoration(27.0%), hypodynamia (21.6%), pharyngalia (10.8%), pharynoxerosis (8.1%), rhinobyon (13.5%), running nose (8.1%), muscular soreness (16.2%), diarrhea (2.7%) and no symptom (16.2%). Fever was the most common symptom (51.40%). The pneumonic changes referred to the latticed ground glass imaging and similar white lung imaging accompanied by consolidated shadows.The rate of pneumonia was high (81.10%). We found that the exclusive percent of eosnophils was abnormally low. By analyzing the correlation of eosnophils, fever and pneumonia, we found that the percentage of eosnophils was low in the COVID-19 patients afflicted withfever or pneumonia(P<0.01).Additionally, pneumonia and fever were negatively correlative with the percentage of eosinophils and eosinophils/neutrophils ratio (P<0.01, respectively), but not associated with pneumonia severity (P>0.05).Fever was not correlated with pneumonia (P>0.05). Conclusion Low percentage of eosnophils may be considered as a biomarker of pneumonia of COVID-19, but not as a biomarker of pneumonia severity.